Boosting SME sales with cash-on-delivery e-commerce and Instagram in Bengkulu: New normal revenue enhancement - Darisna, Vivin; Fadli, Fadli (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
This research aims to examine the extent of the influence of Cash on Delivery (COD)-based e-commerce and Instagram social media on the increase in sales revenue for MSME products in the new normal era. This study employs a quantitative approach with primary data sourced from questionnaires. The research population consists of MSMEs in the city of Bengkulu, totaling 44,472, with a sample size determined using the Slovin formula at 10%, resulting in a sample of 100 MSMEs utilizing COD-based e-commerce and Instagram social media. The collected data are then processed using Smart PLS 4 software. The results indicate that MSMEs using COD-based e-commerce and Instagram social media positively influence the increase in sales revenue for SMEs. Through testing, it is observed that variable X1 has a path coefficient of 0.447 with a p-value of 0.002 < 0.05, and variable X2 has a coefficient of 0.543 with a p-value of 0.000 < 0.05, signifying that these variables positively impact the increase in sales revenue for MSMEs.